Optimising strategy selection for the management of railway assets - Fecarotti, C.; Andrews, J. (2017)
In the railway industry a main concern is how to manage efficiently and effectively the railway assets under budget constraints. Optimal asset management involves decision making and selection of the best inspection, maintenance and renewal interventions for each asset along the network. This paper presents an optimisation method for supporting the decision making process. The method is based on a two-level approach. At a lower level, asset models combining degradation and intervention processes are used in order to evaluate the effects of different intervention strategies on the evolution of the asset state over time. On a system-level, a Knapsack-type optimisation model is developed to selects the optimal combination of intervention strategies to apply to all assets in the network in order to deliver the required level of performance while minimising the whole lifecycle costs.